Foundations of human sociality : economic experiments and ethnographic evidence from fifteen small-scale societies - Henrich, Joseph Patrick (Oxford University Press, 2004)
What motives underlie the ways humans interact socially? Are these the same for all societies? Are these part of our human nature, or influenced by our environments? This text answeres these questions.